2024
DOI: 10.1021/acsami.3c19403
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Fluorescence Materials Based on Naphthalimide-Functionalized Silica Aerogels and Applications in Advanced Information Encryption

Wei Wu,
Yuhui Yang,
Leilei Hu
et al.

Abstract: With the progress of forgery and decryption, the traditional encryption technology is apparent not enough, which strongly requires the development of advanced multidimensional encryption strategies and technologies. Photo-stimuli responsive fluorescent materials are promising as candidate materials for advanced information encryption. Here, we have reported new photo-stimuli responsive materials by encapsulating photochromic molecules spiropyrans (SPs) into naphthalimide-functionalized silica aerogels. By intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Phosphors have different PersL and PL colours, which could provide more optical information to greatly improve anti-counterfeiting performance. 17,18 Recently, Huang and co-workers successfully synthesized an Mn-doped colour-tuneable MgGa 2 O 4 :Zn 2+ /Ge 4+ phosphor using an ion-pair substitution (Zn/Ge → Ga/Ga) method. 19 The characterization results for the phosphor showed that the thermoluminescence (TL) colour of the sample gradually changed from green to red, whereas the PersL colour was green.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphors have different PersL and PL colours, which could provide more optical information to greatly improve anti-counterfeiting performance. 17,18 Recently, Huang and co-workers successfully synthesized an Mn-doped colour-tuneable MgGa 2 O 4 :Zn 2+ /Ge 4+ phosphor using an ion-pair substitution (Zn/Ge → Ga/Ga) method. 19 The characterization results for the phosphor showed that the thermoluminescence (TL) colour of the sample gradually changed from green to red, whereas the PersL colour was green.…”
Section: Introductionmentioning
confidence: 99%